ENVIRONMENTAL ANALYSIS AS A LEARNING RESOURCE FOR JUNIOR HIGH SCHOOL STUDENTS - Maryam paso; Moh. Khadapy Khadapy (Jurnal Ilmu Pendidikan dan Budaya, 2024)
This article aims to analyze the use of the environment as an effective learning resource for junior high school students. A good environment can provide a fun and interactive learning experience, which can increase students' understanding, skills and interest in studying various concepts and topics. In this article, we will discuss the importance of environmental analysis in the education of middle school students and provide several examples of best practices in utilizing the environment as a learning resource. Environmental analysis of learning resources for junior high school students is a holistic approach in evaluating the factors that influence the effectiveness of learning at that level. This analysis abstract includes an understanding of the physical, social, economic and technological conditions that influence the learning environment. Student engagement, diversity, and technology integration are the focus to create richer and more relevant learning experiences. By considering these aspects, environmental analysis aims to improve the quality of education in junior high schools and provide a basis for the development of learning strategies that better suit the needs of students in the modern era. In this article, we will discuss the importance of environmental analysis in the education of middle school students and provide several examples of best practices in utilizing the environment as a learning resource. It is hoped that this article can provide a better understanding of the role of the environment in improving the learning experience of junior high school students and provide real benefits for their development. Environmental analysis as a learning resource for junior high school students plays a crucial role in improving the quality of education